Seven-year follow-up of white-finger symptoms and radiographic wrist findings in lumberjacks and referents. - Kivekas, J.; Riihimaki, H.; Husman, Kaj; Hanninen, K.; Harkonen, H.; Kuusela, T.; Pekkarinen, M.; Tola, Sakari; Zitting, A. J. (Scandinavian Journal of Work, Environment & Health, 1994)
OBJECTIVES--In 1978, a cross-sectional study of 279 lumberjacks exposed to hand-arm vibration and 178 unexposed referents was conducted. The aim of the present study was to provide a seven-year follow-up on (i) the changes in the white-finger symptoms among the lumberjacks and the referents, (ii) the effect of white-finger symptoms on the professional prognosis of the lumberjacks, and (iii) the relationship between hand-arm vibration and changes in wrist bones. METHODS--The methods consisted of a questionnaire, a routine clinical examination, and radiographs of the wrists and hands. The examinations were conducted as a field study using a mobile unit. RESULTS--The prevalence of white-finger symptoms was 18% among the lumberjacks and 3% among the referents in the original study. Seven years later 213 lumberjacks and 140 referents participated in the follow-up. The prevalence of white-finger symptoms was 24.9 among the lumberjacks and 5.7 among the referents, and the seven-year cumulative incidence was 14.7% among the lumberjacks and 2.3% among the referents. After allowance for age, there was no difference in the incidence of white-finger symptoms between the lumberjacks with fewer than 15 years of exposure and the referents, but the risk increased with increasing duration of exposure (risk ratio 8.9, 95% confidence interval 2.5-28.9 for those exposed at least 25 years). There was no difference between the two groups in the prevalence of radiographically detectable translucencies or osteoarthrotic changes in the wrists and hands. CONCLUSION--According to the results, white-finger symptoms are still a problem among lumberjacks who started chain-saw work before 1970.